Family Commuication about Children’s Romantic Relationship - Ayu Martina, Dannia; Lailiyah, S.Sos, M.I.Kom, Nuriyatul (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Romantic relationship becomes a situation that can not be separated from children who get into adolescence life. Most children begin interested to other sex in their teenage lifes and decide to have romantic relationship. Somehow, the issue of romance becomes one of the elements causes a variety of problems and misunderstanding in the family. Those problems arise due to the lack of effective communication about romance, especially between a child and parents. The method used in this reserach is qualitative research with phenomenological approach. The goal of this research is to understand the family communication about children’s romantic relationship. The theories used in this research are Family Relationships Scheme theory, theory of Lie, theory of Love, Close Relationship, and Self Disclosure. The outputs of this research are : (1) Parents from plural family give the right to children to make their own decisions, while parents from consensual family force their children to obey to their decisions, including about romantic relationship (2) Children tend to be more open to their parents when they communicate about daily life (3) The disclousure of children to their parents about romantic relationship, depends on the emotional attachment and the response from their parents when they communicate (4) Communication between children and parents gives influence to the type of love for children (5) Siblings can be a